MANAJEMEN KELAS DENGAN MODEL PENDEKATAN RESTORATIF DALAM MENGELOLA DISRUPTIVE BEHAVIOR SISWA - Iga Dwi Rianningrum; Ima Widiyanah (Jurnal Manajemen Pendidikan, 2025)
Objective: The purpose of this study is to explore the application of classroom management with a restorative approach in managing disruptive student behavior at SMP Hang Tuah 6 Excellent. Qualitative case studies were used in this study to gain a deeper understanding of the restorative principles (reparation, collaboration, and empathy) integrated into classroom management strategies. Data from observations, interviews, and documentation with the principal and teachers were collected as the results of this study. Although traditional disciplinary approaches are still used, the results of the study show that there are several indicators of a restorative approach, such as two-way communication and relationship restoration, which are early signs of the application of a restorative approach that has the potential to reduce disruptive student behavior and build a more positive learning atmosphere.